Computer games for user engagement in attention deficit hyperactivity disorder (ADHD) monitoring and therapy - Craven, Michael P.; Groom, Madeleine J. (2015)
State-of-the-art computer games and psychological tests for symptom monitoring and therapy in Attention Deficit Hyperactivity Disorder (ADHD) are explored and reviewed. Three foci for research studies are identified: task (human performance) focus; educational focus; medical/clinical focus.